Potential for energy recovery of a nonadiabatic subsonic airfoil - Lister-Symonds, Joseph E.; Mutangara, Ngonidzashe E.; Lamprakis, Ioannis; Sanders, Drewan S. (American Institute of Aeronautics and Astronautics (AIAA), 2025)
This paper investigates the effect of wall temperature and flow conditions on the potential for energy recovery of the NACA0012 airfoil. A work–energy balance has been derived from the governing equations for moving control volumes for a body in dynamic equilibrium, aerodynamically decoupled from its propulsive source. The formulation has been applied to an extensive test matrix of computational fluid dynamics cases, with steady level flight imposed and wall temperature, angle of attack, Reynolds number, and Mach number varied independently. The decomposition of the wake energy shows explicitly that the near-field work of the body manifests as global energy constituents, viscous dissipation, and baroclinic work. The analysis identifies the conditions and underlying mechanisms that minimize and maximize the potential for energy recovery, revealing that there are synergistic opportunities for tightly coupled airframe and propulsor configurations with waste heat to reject.
Keywords: Energy Recovery; Computational Fluid Dynamics; Aerodynamic Performance; Airframe/Propulsion Integration; Boundary Layer Ingestion; Aerodynamic Force; Boundary Layer Heat Transfer; NACA Airfoil; Viscous Dissipation; Turbulent Flow; 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; Aerospace & Aeronautics